Updating the OMERACT Filter: Implications for imaging and soluble biomarkers - D’Agostino, Maria-Antonietta (J Rheumatol, 2014)
OBJECTIVE: The OMERACT Filter provides a framework for the validation of outcome measures for use in rheumatology clinical research. However, imaging and biochemical measures may face additional validation challenges due to their technical nature. The Imaging and Soluble Biomarker Session at OMERACT 11 aimed to provide a guide for the iterative development of an imaging or biochemical measurement instrument so it can be used in therapeutic assessment. METHODS: A hierarchical structure was proposed, reflecting 3 dimensions needed for validating an imaging or biochemical measurement instrument: outcome domain(s), study setting and performance of the instrument. Movement along the axes in any dimension reflects increasing validation. For a given test instrument, the 3-axis structure assesses the extent to which the instrument is a validated measure for the chosen domain, whether it assesses a patient or disease centred-variable, and whether its technical performance is adequate in the context of its application. Some currently used imaging and soluble biomarkers for rheumatoid arthritis, spondyloarthritis and knee osteoarthritis were then evaluated using the original OMERACT filter and the newly proposed structure. Break-out groups critically reviewed the extent to which the candidate biomarkers complied with the proposed step-wise approach, as a way of examining the utility of the proposed 3 dimensional structure. RESULTS: Although there was a broad acceptance of the value of the proposed structure in general, some areas for improvement were suggested including clarification of criteria for achieving a certain level of validation and how to deal with extension of the structure to areas beyond clinical trials. CONCLUSION: General support was obtained for a proposed tri-axis structure to assess validation of imaging and soluble biomarkers; nevertheless, additional work is required to better evaluate its place within the OMERACT Filter 2.0.